2016
DOI: 10.1055/s-0036-1587691
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Preoperative Antisepsis with Combination Chlorhexidine and Povidone-Iodine

Abstract: Surgical site infection (SSI) is a significant cause of postoperative morbidity and mortality, increasing length of hospital stay and cost of care. [1][2][3] SSIs are the second most common cause of health care associated infection; U.S. studies have estimated a $45 billion annual cost. 4 Since Joseph Lister popularized the role of preoperative antisepsis in the 1800s, attempts to identify the optimal process and/or agent have resulted in several trials and much scientific tribulation. 5 Despite this effort, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…Various reports on wound infection control have been published, and guidelines have also been provided by the CDC and the UK National Institute for Health and Care Excellence. Regarding skin sterilization before surgery, some studies have shown efficacy for various types of disinfectant, but there remains inadequate evidence with respect to disinfection procedures and amounts of disinfectant used.…”
Section: Discussionmentioning
confidence: 99%
“…Various reports on wound infection control have been published, and guidelines have also been provided by the CDC and the UK National Institute for Health and Care Excellence. Regarding skin sterilization before surgery, some studies have shown efficacy for various types of disinfectant, but there remains inadequate evidence with respect to disinfection procedures and amounts of disinfectant used.…”
Section: Discussionmentioning
confidence: 99%
“…9,[12][13][14][15][16][17] In addition, their application in an alcohol solution as compared with an aqueous solution is probably more effective. This is more clearly the case for CHG. 17 However, we have recently demonstrated through meta-analysis 18 and a large prospective series 19 that CHG in combination with PVI is more effective at reducing surgical site infection than a single agent alone. This is reinforced with precedent that CHG and PVI have different mechanisms of action and efficacy against bacterial and fungal pathogens and ultimately have a theoretical synergistic effect.…”
Section: Preoperative Decolonisationmentioning
confidence: 99%
“…A meta-analysis found that "complete bacterial decolonization" of surgical sites was more likely with sequential use of povidone-iodine and chlorhexidine than either antiseptic alone (odds ratio [OR], 0.18; 95% confidence interval [CI], 0.1-0.31]). 11 This finding may reflect different mechanisms of action of these antiseptic agents. In addition to the aforementioned studies, concurrent use of these antiseptics leads to a greater reduction of Staphylococcus aureus on mucosal tissue compared to either antiseptic alone.…”
Section: 2%mentioning
confidence: 99%